Escaping the Equilibrium: Strategic Innovation as a Deliberate Disequilibrium Mechanism in Oligopolistic Competition - Nurman (PT. Maju Malaqbi Makkarana, 2025)
This study aims to analyze the application of game theory in understanding strategic behavior among firms in an oligopolistic market. Using a qualitative approach with a literature review method, this research examines the concepts of Nash equilibrium, dominant strategy, and price discrimination as foundations for determining optimal strategies among market players. The findings show that game theory, particularly the Cournot, Bertrand, and Stackelberg models, effectively explains competitive interactions in markets with limited participants. Moreover, regulations such as Law No. 5 of 1999 play an important role in maintaining fair competition. Game theory proves to be an effective analytical tool for formulating corporate strategies and economic policies in oligopolistic markets